2021
DOI: 10.1007/s10456-021-09778-6
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel-mediated delivery of microRNA-92a inhibitor polyplex nanoparticles induces localized angiogenesis

Abstract: Localized stimulation of angiogenesis is an attractive strategy to improve the repair of ischemic or injured tissues. Several microRNAs (miRNAs) such as miRNA-92a (miR-92a) have been reported to negatively regulate angiogenesis in ischemic disease. To exploit the clinical potential of miR-92a inhibitors, safe and efficient delivery needs to be established. Here, we used deoxycholic acid-modified polyethylenimine polymeric conjugates (PEI-DA) to deliver a locked nucleic acid (LNA)based miR-92a inhibitor (LNA-92… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 70 publications
(104 reference statements)
0
28
0
Order By: Relevance
“…Based on the critical role of angiogenesis in the post-MI heart, some authors applied gene therapy to stimulate it, exploiting the miR-17-92 cluster [ 188 ]. miR-92a is one of the components of this cluster that negatively regulates endothelial cells and angiogenesis and its expression in ischemic myocardium is increased after MI [ 188 ].…”
Section: Functionalised Acellular Scaffoldsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the critical role of angiogenesis in the post-MI heart, some authors applied gene therapy to stimulate it, exploiting the miR-17-92 cluster [ 188 ]. miR-92a is one of the components of this cluster that negatively regulates endothelial cells and angiogenesis and its expression in ischemic myocardium is increased after MI [ 188 ].…”
Section: Functionalised Acellular Scaffoldsmentioning
confidence: 99%
“…Based on the critical role of angiogenesis in the post-MI heart, some authors applied gene therapy to stimulate it, exploiting the miR-17-92 cluster [ 188 ]. miR-92a is one of the components of this cluster that negatively regulates endothelial cells and angiogenesis and its expression in ischemic myocardium is increased after MI [ 188 ]. Systemic administration of antagomiR-92a in infarcted mice heart promotes angiogenesis, repair of infarct tissue, increases cellular protection and impedes inflammation.…”
Section: Functionalised Acellular Scaffoldsmentioning
confidence: 99%
“…MicroRNAs regulate cancer development and/or drug resistance by targeting mRNAs. In recent years, numerous studies have shown that microRNAs are involved in the regulation of tumor growth, metastasis and angiogenesis in different cancers [13][14][15][16]. Our previous study showed that miR-199 and miR-497 inhibited tumor growth and attenuated chemoresistance in glioma and lung cancers [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…24 Viral vectors are restricted in clinical applications due to their safety issues. Non-viral vectors, which have been widely developed and adopted due to their low virulence and non-immunogenicity, [25][26][27] include cationic liposomes, 28 polyethyleneimine (PEI) 29 and poly (β-amino ester) (PBAE). 30,31 Among non-viral vectors, PBAEs are a widely used type of cationic polymer gene carrier with excellent biocompatibility, good biodegradability, easy production, and low cost.…”
Section: Introductionmentioning
confidence: 99%